Transgenic Expression of IL15 Retains CD123-Redirected T Cells in a Less Differentiated State Resulting in Improved Anti-AML Activity in Autologous AML PDX Models - Mu-Mosley, Hong; Ostermann, Lauren; Muftuoglu, Muharrem; Vaidya, Abishek; Bonifant, Challice L.; Velasquez, Mireya Paulina; Gottschalk, Stephen; Andreeff, Michael (Frontiers in Immunology, 2022)
Immunotherapy with T-cells expressing bispecific T-cell engagers (ENG T-cells) is a promising approach to improve the outcomes for patients with recurrent/refractory acute myeloid leukemia (AML). However, similar to T-cells expressing chimeric antigen receptors (CARs), their antitumor activity is limited in the setting of chronic antigen stimulation. We therefore set out to explore if transgenic expression of IL15 improves the effector function of ENG T-cells targeting CD123-positive AML. T-cells expressing CD123-specific ENG (CD123-ENG) +/- IL15 were generated by retroviral transduction from peripheral blood T cells from healthy donors or AML patients. We characterized in detail phenotype and effector function of ENG T-cell populations in vitro and in vivo. IL15 expressing CD123-ENG (CD123-ENG.IL15) T-cells retained their antigen-specificity and effector function in the setting of chronic antigen exposure for over 30 days of coculture with AML blasts in contrast to CD123-ENG T-cells, which effector function rapidly eroded. Furthermore, CD123-ENG.IL15 T-cells remained in a less differentiated state as judged by a high frequency of naïve/memory stem T-cell-like cells (CD45RA+CCR7+/ CD45RO-CD62L+ cells) without evidence of T-cell exhaustion. Single cell cytokine profiling using IsoPlexis revealed enhanced T-cell polyfunctionality of CD123-ENG.IL15 T-cells in effector cytokines including granzyme B, IFN-γ, MIP-1α, perforin, TNF-α, and TNF-β. In vivo, CD123-ENG.IL15 T-cells exhibited superior antigen specific anti-AML activity and T-cell persistence in both peripheral blood and tissues (BM, spleens, and livers), resulting in a significant survival advantage in one AML xenograft model and two autologous AML PDX models. We demonstrate here that the expansion, persistence, and anti-AML activity of CD123-ENG T-cells can be significantly improved by transgenic expression of IL15, which promotes a naïve/TSCM-like phenotype. However, we also highlight that targeting a single tumor antigen (CD123) can lead to immune escape, reinforcing the need to develop approaches to target multiple antigens. Likewise, our study demonstrates that it is feasible to evaluate autologous T-cells in AML PDX models, which will be critical for the future preclinical evaluations of next generation AML-redirected T-cell therapies.